2019
DOI: 10.1089/jwh.2018.7619
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Academic Productivity and Advancement Among Dental School Faculty

Abstract: Background: An equal number of women and men are now graduating from dental school, but women dentists have lower income and are less likely to achieve positions of leadership, including within dental academia. Materials and Methods: Demographic information and academic rank were obtained for all faculty at the eight dental schools who received the most funding from the National Institute of Dental and Craniofacial Research in 2017. Years since dental school graduation, total number of PubMed-indexed citations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…This research seeks to contribute to understanding of the role of gender in influencing achievement and progression in higher education, by focussing on researchers' decision‐making processes regarding journal choice. Prior research has identified a number of possible factors that might influence the career progression of women in universities, including: bias in hiring academic staff (Van den Besselaar & Sandström, 2016), under‐representation in the academic workforce (Simon et al ., 2019), cultural context (Gomez Cama, Jorge & Andrades, 2016), structural gaps in career advancement for women (Filandri & Pasqua, 2019), and choice of discipline (Thelwall, Bailey, Tobin, & Bradshaw, 2019). Other researchers have focussed more closely on whether the publishing process has any embedded bias (Fox & Paine, 2019; Madison & Fahlman, 2020), and whether editors adopted a ‘gender blind’ approach (Lundine et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This research seeks to contribute to understanding of the role of gender in influencing achievement and progression in higher education, by focussing on researchers' decision‐making processes regarding journal choice. Prior research has identified a number of possible factors that might influence the career progression of women in universities, including: bias in hiring academic staff (Van den Besselaar & Sandström, 2016), under‐representation in the academic workforce (Simon et al ., 2019), cultural context (Gomez Cama, Jorge & Andrades, 2016), structural gaps in career advancement for women (Filandri & Pasqua, 2019), and choice of discipline (Thelwall, Bailey, Tobin, & Bradshaw, 2019). Other researchers have focussed more closely on whether the publishing process has any embedded bias (Fox & Paine, 2019; Madison & Fahlman, 2020), and whether editors adopted a ‘gender blind’ approach (Lundine et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…They are ‘towing the line’ and paying more attention than do men to the expectations placed upon researchers who seek to develop their career. Women understand what they need to do to succeed, but maybe ‘ Being good isn't good enough ’ (Filandri & Pasqua, 2019, p.1), since recent articles still report significant gender differences in output of scholarly publications (Clark & Horton, 2019; Madison & Fahlman, 2020; Simon et al ., 2019; Thelwall, Bailey, Makita, et al ., 2019). According to the UK news media (The Guardian and Nature), this situation has been exacerbated recently by the coronavirus pandemic, during which there are assertions that there is a decline in submission of articles from women, while articles from men have increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, our findings showcased the unique role that personal factors play in influencing nurse faculty recruitment and retention, as it may either hasten or delay decisions of staff nurses from entering academia and/or an experienced faculty to retire (Kirkham, 2016). Although gender was not overtly discussed in any of the reviewed articles, gender-based stress factors are important to address because nursing is a predominantly female-dominated profession and most female academics tend to deal with stress differently (Simon et al, 2019). It is a widely held view that gender differences play important role in faculty work-life and research productivity, and therefore, addressing the gender-based stress factors and issues during the recruitment process and post hire may provide a unique insight and a useful extension to existing research (Counter et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is a widely held view that gender differences play important role in faculty work-life and research productivity, and therefore, addressing the gender-based stress factors and issues during the recruitment process and post hire may provide a unique insight and a useful extension to existing research (Counter et al, 2020). Past studies (Jolly et al, 2014;Simon et al, 2019) found that female academics experience more stress from high expectations, teaching responsibilities, time constraints and general stress compared to men. In particular, non-tenured faculty members appear to experience the most stress and full professors experience the least stress (Cama et al, 2016).…”
Section: Discussionmentioning
confidence: 99%